Identification, recognition and misidentification syndromes: a psychoanalytical perspective - Thibierge, Stéphane; Morin, Catherine (Frontiers in Psychology, 2013)
Misidentification syndromes are currently often understood as cognitive disorders of either the “sense of uniqueness” (Margariti & Kontaxakis, 2006) or the recognition of people (Ellis, Lewis, 2001). It is however necessary to consider how a normal “sense of uniqueness” or a normal people recognition are acquired by normal or neurotic subjects. It will be shown here that the normal conditions of cognition can be considered as one of the possible forms of a complex structure and not as just a setting for our sense and perception data. The consistency and the permanency of the body image in neurosis is what permits that we recognize other people and ourselves as unique beings. These consistency and permanency are related to object repression, as shown by neurological disorders of body image (somatoparaphrenia), which cause the object to come to the foreground in the patient’s words (Thibierge and Morin, 2010). In misidentification syndromes, as in other psychotic syndromes, one can also observe a damage of the specular image as well as an absence of object repression. This leads us to question whether, in the psychiatric disorders related to a damaged specular image, cognition disorders can be studied and managed using the same methods as for neurotic patients.